Pengaruh Leverage Perputaran Modal Kerja Terhadap Profitabilitas Pada PT. Pajjaiang Indah - Mardiana Ibrahim; Andi Bintang Balele; Anastasia Desri Wiwin (OPTIMAL Jurnal Ekonomi dan Manajemen, 2021)
This research aims to determine the effect of working capital turnover on profitability at PT Pajjaiang Indah. The types of data used are qualitative data and quantitative data. The data source used is secondary data. The analytical method used is simple linear regression. The results of this research indicate that there is a significant influence between the influence of working capital turnover on profitability at PT. Pajjaiang Indah concluded that based on statistical analysis, it is known that the company value of simple linear regression is Y=0.48+1.8X and the correlation coefficient of determination (r2) is 0.25 or 25%, which means there is a positive and significant influence, then the test results are based on statistical analysis of the test -t, where it is known that t-count= 0.58< t0 0.48:1=2.353 which Ho rejects and Ha accepts, which means the hypothesis proposed by the author in this research is accepted.